Cell‐free Epstein–Barr virus‐DNA in patients with nasopharyngeal carcinoma: Plasma versus urine. (15th December 2015) - Sengar, Manju; Chorghe, Siddhesh; Jadhav, Kamini; Singh, Shikha; Laskar, Sarbani Ghosh; Pai, Prathamesh; Aggarwal, Jai Prakash; D'Cruz, Anil; Chaturvedi, Pankaj; Deshpande, Mandar; Chaukar, Devendra; Budrukkar, Ashwini; et al.
ABSTRACT: Background: The purpose of this study was to explore urinary Epstein–Barr virus (EBV)‐DNA as a potential biomarker in patients with nasopharyngeal carcinoma (NPC). Methods: EBV‐DNA copies were estimated in plasma/urine of patients with NPC ( n = 76) by real‐time polymerase chain reaction (PCR) at baseline, during therapy, and at follow‐up. Their correlation with EBV‐RNA expression in tissues ( n = 53) was used to assess sensitivity and specificity of plasma/urine EBV‐DNA. Correlation of urine and plasma EBV‐DNA with each other and with radiological response was evaluated. Results: This study demonstrated that urine EBV‐DNA has high sensitivity (96%) at diagnosis and it correlates well with plasma EBV‐DNA at baseline and after neoadjuvant chemotherapy. The EBV‐DNA copies reduced significantly with therapy (plasma: p < .001; urine: p = .011). Patients with low EBV‐DNA copies demonstrated improved survival (plasma: p = .023; urine: p = .083). Conclusion: Plasma EBV‐DNA is a good prognostic marker, whereas further study on a larger cohort may help in developing urine EBV‐DNA as a surrogate prognostic marker for patients with NPC. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1666–E1673, 2016